The Surviving Sepsis Campaign's Revised Sepsis Bundles - Barochia, Amisha V. (2013)
The Surviving Sepsis Campaign (SSC) sepsis care bundles have recently been revised. The original 6-h resuscitation bundle which included rapid antibiotic administration and hemodynamic support with early goal-directed therapy (EGDT) has been divided into two bundles; one including antibiotic and fluid support to be completed within 3 h, and the other including vasopressor support and measures of central venous pressure and oxygen saturation to be completed within 6 h. The original 24-h management bundle targeting glucose control, administration of corticosteroids and recombinant human activated protein C (rhAPC), and limitation of plateau airway pressures during mechanical ventilation is no longer recommended. Past and recent reports by the SSC and others have suggested that compliance with the original bundles was low and their impact unclear. Examination of the revised bundles in the context of issues and questions arising with the original ones suggest that while compliance with new 3-h bundle will be high, compliance with the 6-h bundle will continue to be low.